Is perinatal care in southwestern Ontario regionalized? - Campbell, M K (1991)
OBJECTIVE: To determine whether perinatal care in southwestern Ontario is regionalized, to identify trends over time in referral patterns, to quantify trends in perinatal death rates and to identify trends in perinatal death rates that give evidence of regionalization. DESIGN: Cohort study. SETTING: Thirty-two hospitals in southwestern Ontario (1 level III, 1 modified level III and 30 level II or I). PATIENTS: All pregnant women admitted to the hospitals and their infants. MAIN OUTCOME MEASURES: Antenatal and neonatal transfer status, live-born with discharge home alive from hospital of birth, stillborn, and live-born with death before discharge. RESULTS: Between 1982 and 1985 the antenatal transfer rate increased from 2.2% to 2.8% (p less than 0.003). The proportion of births of infants weighing 500 to 1499 g increased from 49% to 69% at the level III hospital. The neonatal transfer rate increased from 26.2% to 47.9% (p less than 0.05) for infants in this birth-weight category and decreased from 10.2% to 7.1% (p less than 0.03) for infants weighing 1500 to 2499 g. The death rate among infants of low birth weight was lowest among those born at the level III centre and decreased at all centres between 1982 and 1985. CONCLUSIONS: Perinatal care in southwestern Ontario is regionalized and not centralized; regionalization in southwestern Ontario increased between 1982 and 1985.